Beyond Dutch Borders: A Nation in Times of Europeanization - Doomernik, Jeroen (Lidé města, 2014)
Each categorization in population statistics has a bias. Sometimes they deflate and sometimes they expand populations that merit public policy concern. This article discusses the political consequences of policy choices in that respect: notably by the example of Dutch population statistics and the representation of the “allochtoon.” The “allochtoon” (being of foreign origin) was a benevolent creation for it should facilitate monitoring the effects of integration policies. Part of these was easy naturalization. This meant the loss of “nationality” as a statistical marker. Including the migrants’ offspring furthermore rendered “immigrant” useless. However, creating the “allochtoon” also has had unexpected inflationary effects; notably in the public’s perception. First of all, this effect results from the inclusion of the second generation. Secondly: integration polices are exclusively aimed at “allochtonen” with a non-Western background, yet statistical reproduction usually includes all, i.e., also people of Western origin. This inflationary effect is exploited by populist political entrepreneurs hoping to stir concern about alienation in times of Europeanization. The threat of “the others” in the Netherlands is thus easily construed to be much larger than it would be possible if statistics were enumerated differently.